Coal-forming sedimentary model and its control on vertical reservoir heterogeneity of the upper carboniferous Benxi formation in Ordos basin, China - Yaxuan Zhang; Chenjun Wu; Yu Li; Jiabei Li; Chenjun Feng; Bo Li; Zhigang Wen; Xiaona Liu (Scientific Reports)
Abstract The Upper Carboniferous Benxi Formation in the Ordos Basin contains thick coal layers, showing good potential for deep coalbed methane exploration. In this study, we analyze the macroscopic coal type, macerals, industrial composition, and pore characteristics to determine the coal-forming environment and reservoir characteristics of deep coal in the Benxi Formation. Macroscopic Benxi coal types show strong vertical heterogeneity, with a lower layer comprising mainly semi-bright coal, overlain by bright coal, and capped with semi-bright coal and gangue. The ash content of the coal also exhibits strong vertical heterogeneity; from bottom to top, it increases, then decreases, then increases again in the uppermost layer. Vitrinite is the main maceral of Benxi coal, exhibiting the lowest concentration in the lower layer, and increasing in the vertical direction. Obvious vertical heterogeneity also exists in the pore characteristics of the coal, with the total pore volume, total specific surface area, and pore size all varying substantially; the upper layer has the highest porosity with most abundant macropores and micropores. Upper Carboniferous Benxi coal was mainly deposited in a saline, peat-swamp environment, under weak hydrodynamic conditions. The lower layer, controlled by fluctuation of sea level, was deposited in aerobic environment with a certain amount of hydrodynamic force, resulting in the formation of low-vitrinite, high-ash, low-porosity coal with strongly heterogenous characteristics. In contrast, the upper layer was deposited in a reducing, high-level swamp environment during the later stage of a retreating sea. During this stage, a bright coal layer with high vitrinite content, low ash content, and high porosity was deposited under stable conditions and weak hydrodynamic force. Therefore, the upper coal layer exhibits good reservoir properties, conducive to the storage and migration of coalbed methane, and is identified as the key layer for exploration and development of deep coalbed methane in the Ordos Basin. This research provides a theoretical basis for upcoming exploration and development of deep coalbed methane in the Benxi Formation, and provides a reference for future theoretical and technical research that will benefit deep coalbed methane development in other areas of the Ordos Basin.